Effectiveness of Health Education about the Dangers of Cigarettes for Men's Reproductive Health on Interest in Quitting Smoking in Peropa Village, South Kaledupa District, Wakatobi Regency, Southeast Sulawesi Province in 2021 - Hardiawati (Master of Public Health Program Universitas STRADA Indonesia, 2022)
According to the World Health Organization (WHO) report in 2020, tobacco consumption is an important public health challenge for this country. The prevalence of smoking in Indonesia is one of the highest in the world, where 62.9% of adult men smoke. From preliminary research conducted among Peropa residents, out of 100 people, 60 people smoke. In the village they also never received special health education about smoking from anywhere.The design of this research is analytical pre-experiment with an approach for the given post test. Population studied All men aged 16 - 50 years who smoke in Peropa Village, South Kaledupa District, Wakatobi Regency Province Southeast Sulawesi in 2021, totaling 52 people. Independent Variable researched giving HE about the dangers of smoking whereas Variable They depend on smoking interest. The sampling technique uses techniques of probability sampling by simple random sampling, namely taking some samples during research. The results were analyzed using statistical tests wilcoxon The research results obtained values significance (α) is 0.05 with a correlation coefficient of 0.000. Based on hypothesis testing using statistical tests wilcoxon with standards significance (a) =0.05 It can be concluded that there is effectiveness of Health Education about the Dangers of Cigarettes for Men's Reproductive Health on Interest in Quitting Smoking because of the value significance (r) 0,000 greater than α =0.05 Based on value flat-The average attitude after health education is carried out, that health education influences the respondent's attitude to become more positive. The trust given by respondents to researchers in providing health education using leaflets, power points and clip chat can attract the attention of respondents so that they are enthusiastic about following the presentation of the material provided by the researcher and providing something office positive towards the material provided.